Spasmolytic effect of Lonicera japonica extracts on isolated uterus smooth muscle contractions - Hassan Sadraei; Mona Khakboo; Gholamreza Asghari (Shahrekord University of Medical Sciences, 2021)
Introduction: Honeysuckle (Lonicera japonica) is an ornamental flowering plant with numerous traditional medicinal uses. It has been claimed to have anti-spasmodic activities, but only limited studies have been done to support this. The objective of this research was to investigate anti-spasmodic effect of L. japonica flower extract on uterus contractions. Methods: Hydroalcoholic extract was prepared using the maceration technique. In addition, chloroform and ethyl acetate fractions were prepared using a solvent in solvent fractionation technique. Essential oils were collected using the hydro-distillation technique. Rat isolated uterus was suspended in an organ bath and contracted with oxytocin, acetylcholine (ACh), KCl, or application of electrical field stimulation (EFS). The relaxant effects of the extract, its fractions, and nifedipine were examined on uterine contrition induced by the above-mentioned stimuli. Results: Nifedipine in a concentration-dependent manner inhibited uterine contraction induced by oxytocin, KCl, ACh, and EFS. L. japonica flower extract also exhibited an inhibitory effect on the isolated rat uterus. Comparison of the hydroalcoholic extract with its chloroform and ethyl acetate fractions showed that the chloroform fraction was the most potent and the ethyl acetate the weakest part of the plant with antispasmodic activity. The relaxant effect of essential oil had close similarities to that of chloroform extract. Conclusion: Lipophilic compounds isolated by the chloroform partition of crude hydroalcoholic extract of L. japonica flower exhibited the most antispasmodic activity. Ethyl acetate partition of the same extract exhibited the least activity. Therefore, it can be concluded that the spasmolytic constituents of L. japonica flower reside in chloroform partitioning. The nonpolar essential oils may also have a contribution.